Novel in-vessel high rate composter - Hassan, Mohd Ali; Khairul Anuar; Samsu Baharuddin, Azhari; Sulaiman, Alawi; Shafie, Zubair; Abdul Hamid, Hamidi; Sarun, Mohd Fuad; Omar, Shahrudin (2010)

(untitled)
The present invention is an-in-vessel high rate composting apparatus for processing of oil palm biomass, organic and municipal wastes to produce compost product. The composting apparatus consists of a vertical position and cylindrical shape vessel (100) with conical bottom (2) design, materials feeding (1) and product discharge systems (3), a screw impeller (12) for axial mixing, aeration (14) and carbon dioxide (CO2) removal systems and a leachate collection system (15). The optimum composting conditions in the vessel will be maintained by means of programming logic controller (PLC) on key parameters such as temperature, oxygen (O2) level, moisture level and carbon dioxide (CO2) level. The compost product could be let to mature inside the vessel or let to cure elsewhere for the completion of the compost product.